Instrumental analysis of color during storage in dry-cured pork loin produced with swiss chard powder - Aleksandra Silovska Nikolova, Zlatko Pejkovski, Katerina Belichovska, Daniela Belichovska (My University, 2023)
Dry cured meat products hold a rich historical tradition of production and consumption across various global regions. These products have grown to become highly valued and sought after meat items. Multiple factors influence consumers' choices in this regard. Notably, the product's color holds significant importance for consumers. In recent times, there has been a rising trend among consumers to opt for more naturally produced meat products. This research project focuses on examining the color attributes of dry cured pork loin during storage, specifically when Swiss chard powder is used as a natural alternative to nitrites. The study was conducted under industrial conditions and involved the production of five distinct groups of dry cured pork loin: Group I: Table salt, dextrose, Group II: Nitrite curing salt, dextrose; Group III: Nitrite curing salt, BactoFerm Rosa starter culture, dextrose; Group IV: Table salt, Swiss chard powder (manufacturer 1), BactoFerm Rosa starter culture; Group V: Table salt, Swiss chard powder (manufacturer 2), BactoFerm Rosa starter culture. Color measurements were carried out through instrumental analysis after 90 days of storage within the temperature range of 0 to 4°C. The color assessment was conducted on a fresh cross section of the meat at intervals of 60 and 90 minutes at room temperature (20 ± 2°C) and normal daylight conditions. The L value exhibited a range from 28.42 (Group III) to 34.24 (Group I). Over the 120 minute period of analysis, no statistically significant (p ≤ 0.05) changes in L values were observed across all five groups of dry cured pork loin. The group with the highest red color intensity, represented by a value, was Group III (10.86), with starter culture added showing a statistically significant impact on red color development compared to control Group II (9.62). Among the groups incorporating Swiss chard powder, Group IV had an a value of 7.34, while Group V had an a value of 6.72. The group with the least intense b value, indicating yellow color, was Group I (2.11), while the highest b value was observed in Group IV (2.84). The hue, or h value, ranged from 14.050 (Group III) to 34.770 (Group I). Using BactoFerm Rosa starter culture showcased a positive effect on maintaining color stability in dry cured pork loin. Incorporating Swiss chard powder in conjunction with the BactoFerm Rosa starter culture contributed to better color stability, presenting a promising alternative to nitrite usage
Keywords: color stability, dry-cured pork loin, Swiss chard powder